Intraoperative Variations of the Gastrocolic Trunk of Henle noted in Gastrointestinal Surgeries - Ghimire, Roshan; Thapa, Nishant; Acharya, Bidur Prasad; Sah, Bed Prakash; Limbu, Yugal; Regmee, Sujan; Maharjan, Dhiresh Kumar; Thapa, Prabin Bikram (Journal of Nepal Health Research Council, 2024)
Background: The gastro-colic trunk of Henle is a venous trunk that comprises the veins draining the stomach and colon and is an important landmark for various gastro-intestinal surgeries. Understanding the anatomy of these vessels may enhance the surgical outcome. The aim of this study is, to assess the Intraoperative variations of the Gastrocolic Trunk of Henle noted in gastrointestinal surgeries in a tertiary care center.Methods: A descriptive cross-sectional study was conducted at Kathmandu Medical College Public Limited, a tertiary center in Nepal during the period of one year (1st January 2022, to 31st December 2022). All patients undergoing right hemicolectomy, gastrectomy, and pancreaticoduodenectomy were included in the study. Based on per-operative findings, the type of The gastro-colic trunk of Henle was noted during surgery.Results: A total of 49 patients underwent the above-mentioned surgeries during the study period. The gastro-colic trunk was found in 45 out of the 49 patients intraoperatively (91.84%), and the variations were distinguished. The most common configuration noted was the union of the right gastro-epiploic vein, the anterior superior pancreaticoduodenal vein, and the superior right colic vein (Type I), which was noticed in 46.67% of the patients.Conclusions: The intraoperative identification of the anatomy of The gastro-colic trunk of Henle is challenging because of its variable combinations of tributaries. Knowledge of variations in The gastro-colic trunk of Henle is important in preventing intraoperative bleeding, and during identification, the meticulousness of surgery is redefined.Keywords: Gastrocolic trunk of Henle; hemicolectomy; venous drainage.